The Effect of Socio-Economic Factors on the Individual Smoking Status: Case of Indonesia - Nugroho, Prasetyo Ardi; Atmanti, Hastarini Dwi (Jurnal Ekonomi & Studi Pembangunan, 2020)
Research aims to understand the probability the status of smoking and factors that influence individual smoking status in Indonesia. The data used by Indonesian data family life survey (IFLS) 2014 and 2007. The subject of the research is individual 15 aged years or more at 24 province. The study used the sexes, age, marital status, the head of the household status, education, income and the type of individual tribes. Data processing using methods probit regression and was distinctions based on cities and villages. The result showed, sex, the head of a household and education significant impact on the probability of individuals to smoke in cities and villages. Improving education old one year reduce the probability of individuals to smoking of 1.34 percentage points in cities and 0.85 percentage points in the village area. The significance education variable negative shows that education is vital to lower prevalence of smoking.